Comparison of the Effectiveness of Acceptance and Commitment Therapy and Reality Therapy on the Components of Adaptation in Incompatible Married Individuals - Matbou , Azam; Fattahi Andabil, Azam; Dokaneifard, Farideh (Applied Family Therapy Journal (AFTJ), 2025)
Methods and Materials: A quasi-experimental design with a pretest-posttest-follow-up framework was employed, involving two experimental groups (ACT and RT) and one control group. The sample consisted of 54 incompatible married individuals (18 per group) recruited from psychological centers in District 7 of Tehran. Participants completed the Spanier Dyadic Adjustment Scale at pretest, posttest, and follow-up stages. The ACT intervention comprised 8 weekly sessions focusing on mindfulness, acceptance, and value-based actions, while the RT intervention consisted of 8 sessions emphasizing need satisfaction and responsible behavior. Data were analyzed using repeated measures ANOVA to assess changes over time and between groups. Findings: Both ACT and RT significantly improved overall marital adjustment compared to the control group, with significant interaction effects observed for dyadic cohesion (F = 11.161, p = 0.001, η² = 0.247), dyadic consensus (F = 24.787, p = 0.001, η² = 0.422), and affectional expression (F = 22.477, p = 0.001, η² = 0.398). RT demonstrated greater effectiveness in enhancing dyadic cohesion and consensus, while ACT showed stronger outcomes in improving affectional expression. Post-hoc analyses revealed significant mean differences between pretest and posttest for dyadic cohesion in RT (mean difference = -8.167, p < 0.001) and affectional expression in ACT (mean difference = 2.694, p < 0.001). Follow-up assessments indicated sustained improvements, with RT maintaining higher scores in dyadic cohesion (mean = 15.139) and consensus (mean = 25.694), and ACT in affectional expression (mean = 4.78). Conclusion: Both ACT and RT are effective interventions for improving marital adjustment, with RT being more beneficial for addressing behavioral and communication aspects of marital conflict, and ACT more effective in fostering emotional intimacy.